Quality of Health Services at Public Health Center - A. Pananrangi M; Bakri Caco; Suprapto Suprapto (Journal of International Conference Proceedings, 2021)
This study aims to determine the quality of health services at the public health center. The findings of the study revealed that the quality of health services at the public health center was all in the good category (quality). Results: showed that the implementation of the quality of health services at the public health center was seen from the aspects of tangible, reliability, responsiveness, assurance, empathy with good indicators. Suggested implications; that with regional autonomy the performance of public services will be better because the distance between the government and the people being served is getting closer. So that in the future the quality of health services will be maintained.